Comparison of acute recoil after valve deployment and after post‐dilation in patients undergoing transfemoral‐transcatheter aortic valve replacement with SAPIEN‐3 valve. Issue 7 (19th May 2020) - Sammour, Yasser; Kadri, Amer N.; Gajulapalli, Rama Dilip; Kaur, Manpreet; Bazarbashi, Najdat; Banerjee, Kinjal; Karrthik, Antonette; Dhaliwal, Kamalpreet; Burns, Daniel; Yun, James; Krishnaswamy, Amar; Kapadia, Samir R.
Abstract: Background: Transcatheter aortic valves are prone to acute recoil similar to the metal‐based coronary stents. However, it is not clear if recoil remains a factor only after the initial valve deployment or also after post‐dilation. Methods: We conducted a retrospective observational study of patients who underwent transfemoral transcatheter aortic valve replacement (TAVR) with SAPIEN‐3 valve. Acute recoil at the upper, central, and lower levels of the valve was calculated in both anteroposterior right anterior oblique (RAO) and lateral left anterior oblique (LAO) views after initial deployment as well as after post‐dilation. The average recoil of the RAO and LAO views was also calculated and described as RAO/LAO. Results: The acute recoil in the RAO/LAO views (mean ± SD) was 3.9 ± 1.1% after valve deployment in the whole study population ( n = 257). Among the subset of patients who required post‐dilation ( n = 133), the mean acute recoil in the RAO/LAO views was found to be greater after initial valve deployment as compared with after post‐dilation (3.8 ± 1.1% vs. 3.0 ± 0.9%; p < .001). Further, acute recoil was significantly greater in the RAO view than the LAO view and at the central level of the prosthesis as compared with the upper and lower levels. Those findings were consistent after initial deployment as well as after post‐dilation. Clinical outcomes were similar between patients who required post‐dilation compared to those who did not. In multivariable logistic regression analysis, only smaller valve cover index was found to be an independent predictor of 30‐day mild or greater aortic regurgitation (OR 0.007; 95% CI 0.0001–0.707; p = .035). Conclusion: Acute elastic recoil of the SAPIEN‐3 valve was significantly less after post‐dilation as compared with after deployment. It was also greater when measured in the RAO view as compared with the LAO view. Furthermore, acute recoil was not homogenous across the height of the valve stent frame.